Computational and experimental investigations of a cyano group containing novel small molecule organic semiconductor - Goreci, C. Yorur; Kazici, M.; Bozar, S.; Gokce, H.; Gunes, S. (SPRINGER, 2021)
A novel cyano group containing small molecule, namely TAc-Cl was synthesized and characterized. We have performed experimental and Density Functional Theory (DFT) studies to investigate its vibrational frequencies, absorption characteristics and molecular orbital energy levels. Natural Bond Orbital (NBO) and Molecular Electrostatic Potential (MEP) studies through DFT calculations revealed TAc-Cl's potential use as an acceptor molecule. According to electronic energy levels of TAc-Cl molecule obtained from DFT approach, poly(3-hexyl)thiophene (P3HT), which is a conjugated polymer, was selected to be used as donor with novel designed and synthesized molecule for organic solar cells. We have fabricated inverted type organic solar cells and investigated TAc-Cl as a potential acceptor using it as an active layer blended with P3HT in the bulk heterojunction concept.
Keywords: NON-FULLERENE ACCEPTOR; POLYMER SOLAR-CELLS; RECENT PROGRESS; DESIGN; RECOMBINATION; DEPENDENCE; P3HT; Engineering; Materials Science; Physics